Antimicrobial Resistance and Incidence of Integrons in Aeromonas Species Isolated from Diseased Freshwater Animals and Water Samples in Iran - Reza Ranjbar; Reza Salighehzadeh; Hassan Sharifiyazdi (MDPI AG, 2019)
Aeromonas spp. is one of the major pathogens of freshwater animals. There has been little research on the genetics of antimicrobial resistance associated with it in Iranian aquaculture. To remedy this lack in research, 74 multi-drug-resistant Aeromonas spp. were isolated from farmed diseased carp, trout, sturgeon, ornamental fish, crayfish, and corresponding water samples and examined for genomic integron sequences. Class 1 integrons, containing seven types of integron cassette arrays (dfrA1-aadA1, dfrA1-orfC, dfrA12-aadA2, dfrA12-orfF-aadA2, dfrA15, dfrB4-catB3-aadA1, aac(6’)-Ib-cr-arr3-dfrA27) were found in 15% of the resistant isolates; no class 2 integrons were detected in any of the resistant isolates. As some tested isolates were resistant to more than two groups of antibiotics, our results demonstrated that freshwater animals in Iran could be a source of multiply drug-resistant Aeromonas spp. This finding suggests that the origin of the antimicrobial resistance of these animals be placed under increased surveillance in the future and that the use of antimicrobials be limited in aquaculture.